Better sanitation, with communities taking the lead - Muhammod Abdus Sabur (Community Eye Health Journal, 2013)
Over the last 15 years, non-governmental organisations (NGOs) in Bangladesh have pioneered a new approach to sanitation development known as community-led total sanitation (CLTS). This approach has also been replicated in a number of other countries in Asia and Africa. The key difference between previous approaches and CLTS was demand creation within communities.